Faktor Antesenden Perilaku yang mempengaruhi Utilisasi Pelayanan Kesehatan Gigi Ibu Hamil (Studi Pendahuluan di Kecamatan Serpong Tangerang Selatan) - Lisa Prihastari; Peter Andreas (Faculty of Dentistry, Universitas Gadjah Mada, 2015)
Antecendent Affecting Utilization of Dental Services in Pregnant Women (Pilot Study at Serpong District, South Tangerang). Pregnancy and oral health are an aspect that is related to each other. Pregnant women need to regularly check oral health to a dentist every trimester. The number of utilization of dental service which is indicated by pregnant women’s dental visit data in Indonesia is still very low. Antecendent factors in ABC behavior change theory (Antecendent Behavior Consequences) are very important to influence the formation of a behavior including pregnant women dental’s visit. The objective of this study is to identify and evaluate the antecendent factors affecting the utilization of dental services during pregnancy. The preliminary research was conducted at comunity health center in Serpong district, South Tangerang with a cross sectional study. Subjects are 27 pregnant women with gestational age of 4-38 weeks.Data were collected through interview and clinical examination to find out about the score of DMFT index and modified gingival index, which was then analyzed descriptively and statistically using chi-Square test. Results: most of the respondents (96%; 26 respondents) did not visit the dentist during pregnancy. Antecendent factor of pregnant women’s dental visit: not knowing the benefits of dental visit during pregnancy (33%; 9 respondents), having fear of a dentist (26%; 7 respondents), visiting a dentist is thought to be expensive (19%; 5 respondents), having no need (11%; 3 respondents), having fear of causing harm to the fetus (11%; 3 respondents). The mean of DMFT is 2.78 ± 3.23 and the mean of modified gingival index (MGI) 1.00 ± 1.07. There were no significant differences in DMFT and MGI scores of each antecendent (p> 0.05). Conclusion: two major factors predicting the utilization of dental services during pregnancy are 1) knowledge and 2) perceived need.